Altered Expression of BCRP Impacts Fetal Accumulation of Rosuvastatin in a Rat Model of Preeclampsia - Wanying Dai; Micheline Piquette-Miller (MDPI AG, 2024)
Expression of the breast cancer resistance protein (BCRP/ABCG2) transporter is downregulated in placentas from women with preeclampsia (PE) and in an immunological rat model of PE. While many drugs are substrates of this important efflux transporter, the impact of PE associated BCRP downregulation on maternal and fetal drug exposure has not been investigated. Using the PE rat model, we performed a pharmacokinetic study with rosuvastatin (RSV), a BCRP substrate, to investigate this impact. PE was induced in rats during gestational days (GD) 13 to 16 with daily low-dose endotoxin. On GD18, RSV (3 mg/kg) was administrated intravenously, and rats were sacrificed at time intervals between 0.5 and 6 h. As compared to controls, placental expression of Bcrp and Oatp2b1 significantly decreased in PE rats. A corresponding increase in RSV levels was seen in fetal tissues and amniotic fluid of the PE group (p < 0.05), while maternal plasma concentrations remained unchanged from the controls. An increase in Bcrp expression and decreased RSV concentration were seen in the livers of PE dams. This suggests that PE-mediated transporter dysregulation leads to significant changes in the maternal and fetal RSV disposition. Overall, our findings demonstrate that altered placental expression of transporters in PE can increase fetal accumulation of their substrates.